A typical recurrence of rheumatic chorea - Kumar, Gunjan Pankaj; Singh, Ankita; Mulye, Swati (International Journal of Research in Medical Sciences, 2017)
Syndenhams Chorea in acute rheumatic fever is reported to occur in 20-30% of patients. It is usually late onset, occurring upto 6 months after acute infection but may occasionally be present as presenting symptom of rheumatic fever. It is a self-limiting condition with spontaneous remission lasting from 1 week to 6 months. The risk of recurrence is present in 1st 1-2 years in about 20% of cases. Most of children (two thirds) with rheumatic fever are of school age (5-15 years of age). It is common in India and the incidence has not shown the declining trends seen in the developing countries. We report the clinical findings, investigations and the course of clinical development of a 14-year-old girl, who presented with Rheumatic chorea which recurred 3 years after the initial episode.